Validation study for the addition of Cicer arietinum (Desi type) as a species to which the conductivity test for seed vigour can be applied to support Rules proposal C.15.1 - Khajeh-Hosseini, Mohammad (2019)
The conductivity test identified differences in field emergence of 11 seed lots of the Desi type of chickpea (Cicer arietinum). Six of these seed lots, all having a laboratory germination of more than 85%, were tested by four laboratories using the electrical conductivity test, as described in the ISTA Rules (ISTA 2015). All laboratories consistently identified the same significant differences in the seed lot conductivity and the results were repeatable within laboratories and reproducible between laboratories. This provides evidence in support of the addition of Cicer arietinum (Desi type), to the ISTA Rules as a species for which the conductivity test can be applied.